2010
DOI: 10.1097/sla.0b013e3181e495c2
|View full text |Cite
|
Sign up to set email alerts
|

Information Transfer and Communication in Surgery

Abstract: ITC deficits adversely affect patient care. There is a need for standard measures to evaluate this process. Effective and standardized communication among healthcare professionals during the perioperative process facilitates surgical safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 192 publications
(131 citation statements)
references
References 60 publications
5
125
0
1
Order By: Relevance
“…A C C E P T E D M A N U S C R I P T Quality assessment comprised a structured critical appraisal of each paper conducted with the aid of quantitative and qualitative criteria checklists previously employed in similar reviews [15]. For each assessment criterion, articles were scored on a 0 to 3 scale based on the extent to which they met the criteria (0=criteria not met, 1=criteria partially met, 2=criteria definitely met).…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T Quality assessment comprised a structured critical appraisal of each paper conducted with the aid of quantitative and qualitative criteria checklists previously employed in similar reviews [15]. For each assessment criterion, articles were scored on a 0 to 3 scale based on the extent to which they met the criteria (0=criteria not met, 1=criteria partially met, 2=criteria definitely met).…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…Often, surgeons assumed that their equipment would be available and when it was not ready they made up for the delay by cutting corners and potentially compromising surgical safety (Nestel & Kidd). Additionally, results from the systematic review by Nagpal et al (2010) found provider communication to be largely informal during the handoff of patient care in the post anesthesia care unit (PACU). Even more importantly, the transfer of patient information did not always lead to the transfer of patient responsibility.…”
Section: Provider Communicationmentioning
confidence: 99%
“…Improved patient outcomes and decreased hospital admissions directly translate into significant healthcare what information to omit and how to foster a commitment to change practice by all involved caregivers (Nagpal et al, 2010). Most handoff tools are subject to the perception of the healthcare professional being asked to use them .…”
Section: Benefits Of Standardized Handoffsmentioning
confidence: 99%
See 2 more Smart Citations